2023
DOI: 10.3390/su15086587
|View full text |Cite
|
Sign up to set email alerts
|

EWM-FCE-ODM-Based Evaluation of Smart Community Construction: From the Perspective of Residents’ Sense of Gain

Abstract: As a crucial paradigm for addressing urbanization-related problems, smart community construction is in full swing, and its goal is to enhance residents’ sense of gain. Prior studies have not been able to account for all aspects of smart community construction, especially the evaluation tools from the perspective of residents’ sense of gain. Therefore, this paper seeks to establish a comprehensive evaluation framework for residents’ sense of gain in the smart community through the integrated method, which inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Another study identified factors affecting smart community in Beijing, including community hardware, network facilities, system platforms, technology level, resource integration, personnel quality, investment funds, and community residents' awareness levels [58]. Some scholars have devised comprehensive evaluation frameworks for residents' sense of gain in smart communities, integrating methodologies such as the entropy weight method (EWM), fuzzy comprehensive evaluation (FCE), and obstacle degree model (ODM) [59]. Moreover, comparative study of 42 Chinese urban communities is conducted by using the fuzzy set qualitative comparative analysis (fsQCA) method, drawing on the theory of value co-creation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study identified factors affecting smart community in Beijing, including community hardware, network facilities, system platforms, technology level, resource integration, personnel quality, investment funds, and community residents' awareness levels [58]. Some scholars have devised comprehensive evaluation frameworks for residents' sense of gain in smart communities, integrating methodologies such as the entropy weight method (EWM), fuzzy comprehensive evaluation (FCE), and obstacle degree model (ODM) [59]. Moreover, comparative study of 42 Chinese urban communities is conducted by using the fuzzy set qualitative comparative analysis (fsQCA) method, drawing on the theory of value co-creation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This helps healthcare professionals to better coordinate care and provide more personalised healthcare services. Social robots and intelligent assistants [12]. Social robots and intelligent assistants can accompany the elderly and provide assistance in daily life, such as reminders for medication and shopping.…”
Section: The Use Of Digital Technology In Community Ageingmentioning
confidence: 99%
“…Entropy has been widely used to determine the weight of index systems [37,39]. The basic idea of the entropy weight method is to determine the objective weight consistent with the variability of indexes.…”
Section: Calculation Of the Evaluation Index Weight Based On The Entr...mentioning
confidence: 99%